Analysis of Sales Data Visualization of Warung Indomie using the Looker Studio Platform - Rinda Purwenti; Nova Rustiana Bela; Hutri Rizkiyah Alda; Nabila Jihannata (Data Science Insights, 2025)
Indomie stalls are stalls that serve noodles from Indomie products.because people's tastes are very familiar with indomie, the opportunity to do business in the field of warmindo is large.so research was carried out to analyze the sales data of the indomie stall. The method used is Sales Data Visualization Analysis at Indomie Warung Using the Looker Studio Platform, starting from data collection, data preparation and data exploration. The data taken is secondary data from the Bima Putra website. The attributes used are invoice_id,tanggal_transaksi, jenis_produk, quantity, harga_jual, jenis_pembayaran, jenis_pesanan, and nilai_penjualan.so as to produce several visualizations. From this visualization, it is known that the best-selling Indomie product type is Indomie soup with 682 sales and the non-selling product is Indomie Goreng which sold only 293 from January-August 2022. The favorite product is Indomie Soto Betawi flavor as many as 80 sales. With the overall indomie flavor is 18 flavors. For the type of orders that are widely made, delivery is 51.7% with cash payment, which is 20%.the highest monthly income is July 2022 with a total of 1.4 million and the lowest is April 2022 with a total of 899 Rp. With an overall total of 975 sales. Therefore, this indomie stall can pay attention so that the stock of best-selling goods is always available, increase the promotion, improve the service, comfort and facilities of the stall, and of course the taste of the indomie dish should attract customers. Because the factors that cause the success or not of the business come from the number of sales.In addition, from this information, customers can also know which products can be recommended.